Application of Coupled Inductors for Reducing Switching Stresses in a Hybrid Power System - Dharani M; Usha P (Institute of Advanced Engineering and Science, 2015)
This paper presents a novel methodology using coupled inductor for hybridizing multi input sources. A four port three input dc-dc converter is chosen, two photovoltaic sources and a storage medium are interfaced with the converter. The two sources can supply the load as well as charge the battery. Four independently controlled switches are employed to provide dc regulated output. The hybridization of the sources and converter is achieved by coupled inductors. The results show that the presence of coupled inductors increases the voltage gain and reduces the switching stress. The proposed system is verified and validated in MATLAB environment under various operating condition.